2011
DOI: 10.1002/ange.201102872
|View full text |Cite
|
Sign up to set email alerts
|

Sequential SPECT and Optical Imaging of Experimental Models of Prostate Cancer with a Dual Modality Inhibitor of the Prostate‐Specific Membrane Antigen

Abstract: Zwei Techniken, aber nur ein Reagens: Eine einzige Injektion von Verbindung [111In]1 genügt für die auf der Erkennung des prostataspezifischen Membranantigens basierende sequenzielle Radionuklid‐ und optische Bildgebung von Prostatakrebs. Das lässt auf eine rasche Umsetzung des Verfahrens in die klinische Anwendung hoffen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…The feasibility of implementing such a treatment regimen in a clinical work flow was previously demonstrated by van der Poel et al (8), who showed that multimodal indocyanine green-99m Tc-nanocolloids can visualize sentinel lymph nodes. This rather unspecific approach can be overcome by a targeted probe design (21,22). Because of their favorable pharmacokinetic propertiesparticularly, their fast clearance from the blood pool accompanied by high tumor-tobackground contrast at early time pointslow-molecular-weight PSMA inhibitors provide an optimal basis for the design of dual-modality probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of implementing such a treatment regimen in a clinical work flow was previously demonstrated by van der Poel et al (8), who showed that multimodal indocyanine green-99m Tc-nanocolloids can visualize sentinel lymph nodes. This rather unspecific approach can be overcome by a targeted probe design (21,22). Because of their favorable pharmacokinetic propertiesparticularly, their fast clearance from the blood pool accompanied by high tumor-tobackground contrast at early time pointslow-molecular-weight PSMA inhibitors provide an optimal basis for the design of dual-modality probes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the upregulation of PSMA correlates with the malignancy of the carcinoma (10), PSMA became an established target for the diagnosis and therapy of prostate cancer. Besides monomodality probes providing either radionuclide (11)(12)(13)(14)(15)(16) or fluorescence imaging (17)(18)(19)(20), only a few antibody-or small-molecule-based dual-modality agents targeting the extracellular domain of PSMA have been designed (21,22). However, in antibody approaches, specific tumor visualization is hampered by the long circulation in the blood pool, whereas small-molecule probes show fast pharmacokinetics resulting in clear imaging contrast at early time points after injection.…”
mentioning
confidence: 99%
“…Unlike PSA, PSMA expression reliably increases following androgen ablation [14,16]. Therefore, PSMA has become a rapidly expanding target for imaging and therapy in both pre-clinical and clinical settings and has been the target of several FDA approved imaging agents [17][18][19][20][21][22][23][24][25]. None of the available genetically engineered murine models of spontaneous prostate cancer form tumors that express PSMA, which is a substantial deficiency of these models, also making them unsuitable for evaluation of emerging PSMA-targeted diagnostics and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, significant efforts have been devoted to developing multimodal imaging probes in the past decades 5. One general approach is to integrate different functional small molecules together using elegant synthetic strategies 5d. 6 For example, Banerjee et al.…”
mentioning
confidence: 99%
“…6 For example, Banerjee et al. reported a small‐molecule‐based dual modality SPECT/near‐infrared fluorescence (NIRF) imaging agent, which shows high and specific uptake in prostate‐specific membrane antigen (PSMA) positive xenografts and excellent pharmacokinetics for targeting PSMA in vivo 5d. As a parallel direction, nanoparticle (NP) based multimodal imaging probes have also attracted great attention because inorganic NPs typically exhibit large surface/volume ratios, tunable and diverse material properties 5e.…”
mentioning
confidence: 99%